Ecological characterization of soil macrofauna in two evergreen forest sites at El Salón, Sierra del Rosario, Cuba - Cabrera Dávila, Grisel de la C; López Iborra, Germán M (BOSQUE, 2018)
The richness, abundance, diversity and functional composition of soil macrofauna were studied in two sites of the evergreen medium forest (Helechal and Vallecito), located at the Ecological Reserve El Salón from Sierra del Rosario; they were analyzed with respect to other land use systems evaluated in Cuba. The macrofauna was collected in situ from 25 × 25 × 20 cm monoliths extracted from the soil. In this type of ecosystem, 34 families of the edaphic macrofauna belonging to 18 orders were found. The Vallecito site showed higher families richness, density and diversity of the macrofauna (34 families, 1,298.5 individuals m-2 and H’ = 2.72) compared to Helechal (19 families, 749.2 individuals m-2 and H’ = 2.57). Although, only richness showed significant differences between the two locations. The seasonality in the sampling marked the variations between the sites, which was carried out during a rainy month in Helechal (October 2009) and during a dry month in Vallecito (March 2011). The functional composition of the edaphic community was similar in both sites, where the most outstanding guilds were litter detritivores, soil engineers and predators. However, the dominant families within each functional group changed between sites. The structure found of the macrofauna was very similar to those of other tropical forests, and hardly changed in relation to secondary forests studied in Cuba, although it did change in relation to more disturbed systems such as pastures and crops.